Review of national laws and regulation in Indonesia in relation to an ecosystem approach to fisheries management. (May 2018) - Muawanah, Umi; Yusuf, Gellwynn; Adrianto, Luky; Kalther, Jimy; Pomeroy, Robert; Abdullah, Habibi; Ruchimat, Toni
Abstract: The Government of Indonesia, through the Ministry of Marine Affairs and Fisheries, considers an ecosystem approach to fisheries management (EAFM) to be the preferred option and best practice for the long-term sustainability of fisheries and the ecosystem services provided to society. Recognizing that an appropriate legal, policy and institutional framework must be in place for an EAFM, this paper presents a review of current Indonesian laws and policies for an EAFM; an assessment to identify gaps, challenges and opportunities for an EAFM; and recommendations for EAFM implementation. A strong co-management structure of the fishery management area (FMA) governance is at the heart of EAFM implementation. It is also critical to mention the governance or institution structure of Fishery Management Council of FMA in Indonesian waters in the new proposed fishery law.